THE PROJECT OF DOCTOR ABDAH AL- RAJIHI IN FACILITATING AND TEACHING ARABIC GRAMMAR: AN ANALYTICAL STUDY - Al- Khazrajy, Abid Al- Baqi (International Journal of Psychosocial Rehabilitation, 2020)
There were several and many attempts by modern scholars to renew the grammatical consideration, which were known as the efforts of grammar facilitation. Admitting the efforts of their owners and acknowledging their favor, however, these efforts were not conscious to present a comprehensive alternative to the inherited grammatical model ''induction to Arab speech.'' This is due to a weakening of interest in the statement of grammar theory; in addition, to the confusion between the principals of the grammar endoscopy and what it requires as the requirements of the grammar lesson and its teaching. Renewal requires grammatical diligence will be as introduction to facilitation and the separation between the theory and the practice is paved for it and this is what we stood on at the late Professor doctor Abdah Al- Rajiji, in his kind attempts to facilitate the Arabic grammar, without calling it with ''facilitated'' in his discipline with theory of grammar and his respect for its early pioneers and away of theorizing, rather, it is starting from the text, in preparation for facilitation. ''The putting of the modern researcher's fingers in his ears in front of the achievements of contemporary humanities is considered as an explicit violation of the old heritage movement itself, and it would be a betrayal of the trustworthiness of it to keep it strong and able to work   therefore, the building – and because of it is building- urgently in need of re- care.